Valorization of water treatment sludge for applications in the construction industry: a review - Mattoso, Ana Paula (2024)
To address the growing global water demand, it is imperative to implement advanced treatment systems and sustainable alternatives for managing the large amount of waste generated during the water purification process, known as water treatment sludge (WTS). Worldwide, researchers and companies are exploring alternatives and methods for the valorization of WTS as a raw material in other processes. It is urgent that all productive sectors, which contribute significantly to greenhouse gas emissions, adopt this management principle to ensure more sustainable production, contributing to the global goal of climate neutrality. Notably, in civil construction, incorporating WTS as a supplementary cementitious material (SCM) shows great promise, considering that the industrial waste currently used for this purpose is increasingly restricted. The use of WTS as a raw material in the cement industry not only contributes to the reduction of the carbon footprint, but also reduces the high waste load still disposed of in landfills. The emerging applications for WTP sludge are reviewed, with emphasis on its valorization in the civil construction as an SCM. The main characteristics of this waste and their impacts on the environment are also addressed.